The Coevolution of Fungal Mitochondrial Introns and Their Homing Endonucleases (GIY-YIG and LAGLIDADG) - Megarioti, Amalia H (Genome Biol Evol, 2020)
Fungal mitochondrial (mt) genomes exhibit great diversity in size which is partially attributed to their variable intergenic regions and most importantly to the inclusion of introns within their genes. These introns belong to group I or II, and both of them are self-splicing. The majority of them carry genes encoding homing endonucleases, either LAGLIDADG or GIY-YIG. In this study, it was found that these intronic homing endonucleases genes (HEGs) may originate from mt free-standing open reading frames which can be found nowadays in species belonging to Early Diverging Fungi as “living fossils.” A total of 487 introns carrying HEGs which were located in the publicly available mt genomes of representative species belonging to orders from all fungal phyla was analyzed. Their distribution in the mt genes, their insertion target sequence, and the phylogenetic analyses of the HEGs showed that these introns along with their HEGs form a composite structure in which both selfish elements coevolved. The invasion of the ancestral free-standing HEGs in the introns occurred through a perpetual mechanism, called in this study as “aenaon” hypothesis. It is based on recombination, transpositions, and horizontal gene transfer events throughout evolution. HEGs phylogenetically clustered primarily according to their intron hosts and secondarily to the mt genes carrying the introns and their HEGs. The evolutionary models created revealed an “intron-early” evolution which was enriched by “intron-late” events through many different independent recombinational events which resulted from both vertical and horizontal gene transfers.